Synergistic effects of chemical and biochemical fertilization on yield enhancement and oil quality optimization in ‘Zard’ olive cultivars - Tadayon, Mohammad Saeed; Asgharzadeh, Ahmad; Mousavi, Seyed Majid; Saghafi, Kobra (Frontiers in Plant Science, 2025)
PurposeThis research evaluates the combined impact of chemical and biological fertilizers on ‘Zard’ olive trees, aiming to reduce chemical dependency, enhance fertilizer efficiency, and improve nutritional value, yield, and oil quality from 2020 to 2023.MethodA factorial design within a randomized complete block was used, focusing on the first factor, soil chemical fertilizer application (CF) at three levels, 100% (CF100), 75% (CF75), and 50% (CF50) of the fertilizer requirement as determined by soil testing. This was coupled with foliar applications of 20-20-20 NPK fertilizer with micronutrients. The second factor, biological fertilizer application (BF), also comprised three levels: BF0 (control), soil-applied organic fertilizer without biological agents; BF1, which included a soil application of an organic fertilizer mix, mycorrhizal fungi, and the beneficial bacteria Bacillus subtilis and Pseudomonas fluorescens, supplemented with fulvic acid and amino acids; and BF1+BFF, where trees were treated with both soil and foliar applications of the aforementioned bacterial species, fulvic acid, and amino acids.ResultsThe CF100+BF1+BFF treatment significantly increased fruit length (31.14%), diameter (41.61%), flesh thickness (30.48%), fresh weight (38.76%), dry weight (55.68%), and yield per tree (27.00%) compared to the control (CF100+BF0). Principal Component Analysis (PCA) identified CF100+BF1+BFF, CF75+BF1+BFF, and CF50+BF1+BFF as superior treatments for fruit characteristics, while CF50+BF1+BFF excelled in oil quality indicators.ConclusionThe study recommends the CF75+BF1+BFF and CF50+BF1+BFF treatments for concurrent improvements in fruit and oil quality. The combined use of biological fertilizers with reduced chemical fertilizers is considered the superior and optimal approach for fertilizing ‘Zard’ cultivar olive orchards.